Secure encryption in network using Data Encryption Standard (DES) for high security transmission - Abdullah, Nur Amila (2017)
Network security have become as significant issue in the recent years. In the field of network security, the role of cryptography is most important. A secrecy key and shared key algorithm is known as a symmetric key algorithm. This is because, in symmetric key algorithm a shared key does both the encryption and decryption. However, there are some weakness of that technique such as if the key is known to others the entire conversation is compromised. In data security system, encryption has become a solution and act as significant role providing the security. The Data Encryption Standard (DES) algorithm is a symmetric key algorithm for the encryption of electronic and allowed for information. The objective of this paper is to improve the security data by using DES algorithm. The substitution technique is applied with addition a XOR operator to enhance the DES algorithm as proposed. Substitution cipher is a technique of encoding where units of plain text are replaced with cipher text and XOR operator is one of the encryption process used to make the cipher text harder to decryption. The result has been compared and analysed by using method, encryption strength, message length and encryption time. The strength level is higher because of used the Extended ASCII-code with 256 character length bit and addition with the 8-bit binary key to break the cipher text. Hence, the analysis are obtained when the message length is long around 40 to 188, the encryption time has been achieved the limitation time. The graph that can be show is static .To summarize it, all this technique are useful for real time encryption. The security provided by this algorithm can be enhanced further, if more than one algorithm is applied to data.